Effects of Current Density on Defect-Induced Capacity Fade through Localized Plating in Lithium-Ion Batteries - Liu, Xinyi M.; Arnold, Craig B. (Journal of the Electrochemical Society, 2020)
Because of material heterogeneity and non-uniform ion transport, lithium plating, the formation of metallic lithium, can sometimes occur only in specific locations. Such localized plating can significantly reduce battery capacity through locally accelerated aging and also imposes safety concerns. In this work, we investigate the effects of current density on localized plating through experimental studies and numerical simulations, and demonstrate the plating results using LCO/graphite coin cells. As the current density increases, the critical size that triggers non-uniform plating decreases, and we directly correlate size and current density to capacity fade of a battery. We also identify transitions from no plating, to heterogeneous plating, and to homogeneous plating. We show that diffusion plays a critical role in the aggregation of lithium, and the critical size is negatively correlated with current density and the effective diffusion length. This work can provide insights into the quick charging of batteries that are subject to material defects or non-uniform current distributions.